Delayed presentation of congenital diaphragmatic hernia in children: case series and review of the literature - Ghritlaharey, Rajendra K.; Chaubey, Yogshri (International Journal of Research in Medical Sciences, 2023)
Congenital diaphragmatic hernia (CDH) is the most common developmental defect of the diaphragm. Ten to 20% of CDH cases may clinically present later in life, after the neonatal period. This study aims to review the demographics, clinical characteristics, various radiological investigations carried out for the diagnosis, and outcome of the surgical therapy offered for the treatment of late-presenting CDH in children. This study is a retrospective, descriptive study of the children diagnosed with CHD, clinically presented late after the neonatal period, and were surgically treated. These children were admitted and managed in the author’s department of pediatric surgery between January 2019 and September 2023. During the study period, n=5 children (n=3 boys and n=2 girls) were diagnosed as delayed-presenting CDH and were operated upon by the authors. Their age ranged from two to ten months, with a mean of 5.6 months. Four children were diagnosed with left-sided CDH and one of the children with a right-sided CDH. All the children were operated upon through the abdominal incision. The reduction of the hernia contents into the peritoneal cavity and primary repair of the diaphragmatic defect was carried out successfully in all the children. The postoperative recovery was excellent for all the cases. All five children did well during the follow-up period, ranging from one month to four years. Children diagnosed with a delayed-presenting CDH, clinically presented with vague symptoms. Surgical therapy offered for the management of the delayed-presenting above-mentioned CDH cases carries an excellent result.